ANALYSING THE BIOCATALYTIC ASPECT OF AMYLASE FROM PLANT AND MICROBIAL SOURCES FOR INDUSTRIAL APPLICATION - NIHARIKA, DIGUMARTHY; JAIPURIAR, DIPTI SONI; VAISHNAV, VIRENDRA (International Journal of Current Pharmaceutical Research, 2020)
Objective: Biocatalysts have a wide role in industries and amylases are one of the best enzymes used in various industries as they stay stable physically and chemically even under environmental or physical stress. Extraction of amylase from plant sources like chickpea and green pea and also the microbial source of Bacillus subtilis. Methods: Enzymatic activity was determined by enzyme assay and purified through the following steps such as salt precipitation, dialysis, Ion-exchange chromatography and characterized using SDS PAGE. Results: Enzymatic activity of amylase produced by bacillus subtilis was determined the highest (4600 U/ml) activity and molecular weight 48.9kDa was recorded. Conclusion: Amylase is a highly important enzyme that breaks down the starch molecules into simple sugars. It has potential in a wide range of industrial processes such as food, fermentation and pharmaceutical industries. All the sources used in this study proves that the bacteria have the highest concentration of enzyme in the form of protein.